Dwindling Catla catla population of Gobindsagar reservoir - Kaushal, D K (Indian Journal of Fisheries, 2011)
Fish productivity of a reservoir largely depends on scientific exploitation and management offish stocks present Therefore, an accurate understanding of the nature and fluctuations in the population of fishes is necessary for undertaking a fisheries development programme. The studies on the fisheries of Gobindsagar reservoir had earlier been done by Rao and Kaushal (1982) and Kaushal and Tyagi (1988). The present study was done to examine the causes for the decline of catla fishery vis-a-vis remedial measures for its rehabilitation in Gobindsagar, a reservoir on the rivCT Sutlej at latitude 31Â° 25’N and longitude 76Â° 25’E.